Pengembangan UMKM dan Ekonomi Kreatif di Tengah Pandemi Covid-19 - Divo Sangrila Yusuf; Ade Yunita Mafruhat (UNISBA Press, 2023)
Abstract. Covid-19 is a disease outbreak that has spread almost all over the world, especially Indonesia. The existence of the Covid-19 pandemic has greatly affected the community's economy, especially in the field of MSMEs and the creative economy. Thus, there is a need for business development in the midst of the Covid-19 pandemic which can increase MSMEs and the creative economy amid the current conditions. This study uses a qualitative type research method with data sources derived from secondary data, including: books, journals, and other credible sources. Based on the results and discussion, it is known that the Covid-19 pandemic has greatly impacted the condition of MSMEs and the creative economy. Due to the pandemic, many businesses cannotsurvive and ends roll level. This is because the level of sales has decreased dramatically. Thus, it is necessary to develop SMEs and the creative economy, including: carrying out marketing by utilizing digital media, product promotion policies in the form of packages at relatively affordable costs, updating products so that they are more attractive to consumers, and optimizing services to consumers. Thus, it is hoped that MSMEs and other creative economies can rise and develop amid the Covid-19 pandemic. Abstrak. Covid-19 merupakan wabah penyakit yang menyebar hampir di seluruh dunia, terutama Indonesia. Adanya pandemi Covid-19 sangat mempengaruhi perekonomian masyarakat, terutama di bidang UMKM dan ekonomi kreatif. Sehingga, diperlukan adanya pengembangan usaha di tengah pandemi Covid-19 yang dapat meningkatkan UMKM dan ekonomi kreatif di tengah kondisi sekarang ini. Penelitian ini menggunakan metode penelitian jenis kualitatif dengan sumber data yang berasal dari data sekunder, diantaranya: buku, jurnal, maupun sumber-sumber kredibel lainnya. Berdasarkan hasil dan pembahasan diketahui bahwa pandemi Covid-19 sangat berdampak pada kondisi UMKM dan ekonomi kreatif. Akibat pandemi, banyak usaha yang tidak dapat survive dan berakhir gulung tingkat. Hal itu dikarenakan tingkat penjualan yang semakin menurun drastis. Sehingga, dibutuhkan pengembangan UMKM dan ekonomi kreatif, diantaranya: melakukan pemasaran dengan memanfaatkan media digital, kebijakan promosi produk berbentuk paket dengan biaya yang relatif terjangkau, memperbarui produk sehingga lebih menarik minat konsumen, dan optimalisasi pelayanan kepada konsumen. Dengan demikian, diharapkan UMKM dan ekonomi kreatif lainnya dapat bangkit dan berkembang di tengah pandemi Covid-19.